PENGARUH HARGA, LOKASI, PROMOSI DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN - Wildayanti Wildayanti; Dwi Ayu Lestari; Herwanita Herwanita; Ayu Rahmayanti; Andi Hamniza Kastury (Universitas Ichsan Sidenreng Rappang, 2026)
This research discusses the influence of price, location, promotion and facility on housing purchase decisions (a study at PT. Sitawala Rio Rennu Perumahan Rezky Graha 2 Watampone). The objective of this research is to determine the influence of price, location, promotion and facility on purchase decisions for Perumahan Rezky Graha 2 Watampone. This research is a quantitative research using an Islamic economics and a sociological approach. The number of respondents is 70. The data collection techniques are questionnaires, observation and documentation. The data analysis technique is multiple linear regressions to determine the influence of price, location, promotion, and facility variables on housing purchase decisions. The results showed that the price and promotion variables had no significant effect on purchase decisions while the location and facility variables had a significant effect on purchase decisions. While, simultaneous testing showed that the price, location, promotion and facility variables had a significant effect on purchase decisions. Based on the results, it can be implied that the location and facility variables are aspects that must be maintained and even need to be further improved so that housing purchase decisions also increase. For the price and promotion variables, the developers must consider the sales price and sales promotion.